Ultrasound-guided percutaneous retrieval of non-radiopaque radial line using a microsnare - Hasan Alaeddin; Amr Elsaadany; Mohammad Rashid Akhtar (CVIR Endovascular, 2023)
Abstract Radial arterial lines are inserted in critically ill patients admitted to hospital intensive care units for continuous monitoring of their blood pressure. On removal the line can rarely become transected, potentially leading to thrombosis of the radial artery. Retrieval of the broken fragment can be achieved by open surgery, however other retrieval methods using ultrasound-guidance have been performed as they are considered safer and less invasive. We describe our technique of ultrasound-guided percutaneous retrieval of a broken non-radioopaque radial line in one patient, which involved the use of a microsnare. Under local anaesthesia and ultrasound guidance, a 6 Fr 5.5 cm short brite tip sheath was introduced into the radial artery, followed by a microsnare which was used to capture the arterial line, track the line back into the sheath and remove it uneventfully. The use of a microsnare under ultrasound-guidance is only one method to retrieve transected radial lines, with other interventional methods described in the literature. It enables a minimally invasive and safer approach to this potentially critical challenge and can help affected patients avoid open surgery to achieve the same management outcome.